Suicidal behavior of immigrants and ethnic minorities in Europe - Bergen, Diana D. van (Hogrefe, 2015)
Leading experts examine suicidal behavior and its prevention in immigrants and their descendants the fastest expanding proportion of the population in many European countries. Nearly half of the inhabitants of several large European cities, such as London, Berlin, or Amsterdam, and a rising proportion of many countries overall population, are immigrants or from an ethnic minority. However, this fact has been understudied in research and prevention of suicidal behavior. This volume addresses this gap. Leading experts describe rates and risk factors of suicidal behavior among immigrants and ethnic minorities, looking at high-risk groups such as female immigrants and refugees, as well as examining the role of cultural factors. They also show how epidemiology, theory, and other research findings can be translated into solid prevention and treatment programs. -- Provided by publisher